Analisis Buku Ajar “Aku Cinta Bahasa Arab” : Perspektif Seleksi, Gradasi, Repetisi, dan Presentasi Materi Ajar - Khotimatul Husna; Fatkhurrohman, Fatkhurrohman; Asep Sunarko; Rifqi Aulia Rahman (PT. Berkah Smart Academica, 2025)
Amid the rapid globalization and technological advancements, Arabic language teaching in Indonesia still faces significant challenges, including the lack of effective textbooks that align with students' needs. This study aims to analyze the textbook Aku Cinta Bahasa Arab for Grade VI Madrasah Ibtidaiyah by Agus Wahyudi in terms of selection, gradation, repetition, and presentation of teaching materials. This topic was chosen due to the importance of developing high-quality textbooks to support the Arabic language learning process in Indonesia, particularly at the Madrasah Ibtidaiyah level. This research employs a qualitative approach with a literature study method, gathering and analyzing data from relevant textbooks and other supporting sources. The primary data analyzed is the Aku Cinta Bahasa Arab textbook published by PT Tiga Serangkai Pustaka Mandiri, along with secondary references that support this study. Data analysis is conducted using two main methods: content analysis and discourse analysis, to identify the characteristics of the teaching materials and the relationship between the messages in the textbook and students' understanding. The results indicate that the textbook meets the criteria for good selection, gradation, repetition, and presentation of material, with content appropriate for the cognitive development level of Grade VI students. However, there are some shortcomings, such as the absence of practice books and the lack of clear usage guidelines for teachers. This study concludes that although the textbook meets the standards as an effective learning resource, there are aspects that need improvement, such as the diversity of supporting media and consistency in visual presentation.